Rhodotorula mucilaginosa Fungemia, a Rare Opportunistic Infection without Central Venous Catheter Implantation, Successfully Treated by Liposomal Amphotericin B - Ryuichi Hirano; Tatsuro Mitsuhashi; Katsuyoshi Osanai (Case Reports in Infectious Diseases)
Background. Fungemia due to Rhodotorula mucilaginosa is rare and highly resistance to antifungal therapy. Since most cases of R. mucilaginosa fungemia are attributed to medical devices, limited information is currently available on infection without central venous catheter (CVC) implantation. We herein report a case of R. mucilaginosa fungemia without implantation of CVC, successfully treated by liposomal amphotericin B (L-AMB). Case Presentation. An 81-year-old man with a history of chronic obstructive lung disease and rheumatoid arthritis was admitted with dyspnea and fever. The present case had no previous history of CVC implantation. Candidemia was suspected based on yeast and salmon-pink colonies in blood cultures, and thus, micafungin (MCFG) was administered. The isolated yeast was identified as R. mucilaginosa, which exhibited resistance to MCFG. Therefore, antifungal therapy was changed to L-AMB. The sterile blood culture and defervescence were observed from the initiation of L-AMB. Conclusion. Although the obvious entry point was unclear, long-term immunosuppressive therapy for RA may have damaged the gastrointestinal tract, which leading to the bacterial translocation of R. mucilaginosa. An early class switch to L-AMB was effective. Physicians need to consider the administration of L-AMB in cases suspected of R. mucilaginosa fungemia following the detection of salmon-pink colonies in blood cultures.